2016
DOI: 10.1166/jbn.2016.2202
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Templated Growth of Bone Minerals from Modified Simulated Body Fluid on Nanofibrous Decellularized Natural Tissues

Abstract: Small intestine submucosal (SIS) membrane used in this study is a decellularized, naturally occurring nanofibrous scaffold derived from a submucosal layer of porcine small intestine. It is predominantly composed of type I collagen fibers. Here we studied the bio-templated growth of hydroxylapatite (HAP) bone minerals on the SIS membrane from a modified simulated body fluid (1.5 SBF) at the body temperature, namely, under a near-physiological condition, in order to evaluate its bone bioactivity, the capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
0
17
1
Order By: Relevance
“…In conjunction with a previous study showing that charged materials can act as nucleation points for mineralization 47 , we conclude that the charged amino groups introduced by cationization into the cBSA can serve as nucleation points to favor mineralization. Interestingly, despite several studies showing that in vitro mineralized scaffolds including fibrous scaffolds support the osteogenic differentiation of MSCs, we obtained contradictory results 10,48,49 . Our experiments revealed that in vitro mineralization of the cBSA-fibers which covered the entire growth surface did not support the osteogenic differentiation to a higher extent than TCP characterized by an increase of the osteogenic marker OCAL or the ALP activity.…”
Section: Discussioncontrasting
confidence: 77%
“…In conjunction with a previous study showing that charged materials can act as nucleation points for mineralization 47 , we conclude that the charged amino groups introduced by cationization into the cBSA can serve as nucleation points to favor mineralization. Interestingly, despite several studies showing that in vitro mineralized scaffolds including fibrous scaffolds support the osteogenic differentiation of MSCs, we obtained contradictory results 10,48,49 . Our experiments revealed that in vitro mineralization of the cBSA-fibers which covered the entire growth surface did not support the osteogenic differentiation to a higher extent than TCP characterized by an increase of the osteogenic marker OCAL or the ALP activity.…”
Section: Discussioncontrasting
confidence: 77%
“…Compared with other reported natural bio-templates for biomorphic synthesis of hydroxyapatite (bamboo, rattan [32]), ESM is widely available, considered waste, and is a source of natural collagen, chondroitin and hyaluronic acid [33]. Porcine small intestine submucosal (SIS) membrane was also recently reported as bio-template, due to its complex architecture of type I collagen fibers, but the obtained results do not demonstrate its ability to induce in vivo biomineralization [34].…”
Section: Introductionmentioning
confidence: 92%
“…The preferential growth of HAp crystallites was previously observed during the precipitation of HAp in the presence of templating organic molecules, such as poly(acrylic acid), [ 61 ] amino acids (glycine and glutamic acid), [ 62 ] and decellularized natural tissues. [ 63 ] Accordingly, highly crystalline HAp crystallites could be developed onto the surfaces of MNPs agglomerates. This was reflected on the preservation of the composition of the magnetic core with preserved magnetic properties, which could be attributed to the existence of co‐operative magnetization.…”
Section: Resultsmentioning
confidence: 99%